2020
DOI: 10.1007/s00167-020-06288-8
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine combined with suprascapular nerve block and axillary nerve block has a synergistic effect on relieving postoperative pain after arthroscopic rotator cuff repair

Abstract: Purpose Suprascapular nerve block (SSNB) is the most commonly used block for the relief of postoperative pain from arthroscopic rotator cuff repair and can be used in combination with axillary nerve block (ANB). Dexmedetomidine (DEX) is a type of alpha agonist that can elongate the duration of regional block. The aim of this study was to compare the effects of the use of dexmedetomidine combined with SSNB and ANB with those of the use of SSNB and ANB alone on postoperative pain, satisfaction, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…High-dose peripheral dexamethasone may also lead to a risk of wound infection and neurotoxicity ( 8 ). Perineural application of dexmedetomidine in arthroscopic rotator cuff repair can reduce postoperative pain scores and delay rebound pain during the first 48 post-surgical hours ( 9 , 10 ). Combining two or more nerve blocks and prolonging the block duration significantly reduces rebound pain and oral opioid use ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…High-dose peripheral dexamethasone may also lead to a risk of wound infection and neurotoxicity ( 8 ). Perineural application of dexmedetomidine in arthroscopic rotator cuff repair can reduce postoperative pain scores and delay rebound pain during the first 48 post-surgical hours ( 9 , 10 ). Combining two or more nerve blocks and prolonging the block duration significantly reduces rebound pain and oral opioid use ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dexmedetomidine (DEX), a selective agonist of α2-adrenergic receptors, can be an effective adjuvant to local anesthetics for peripheral nerve blocks [ 22 , 23 ]. Preclinical and clinical studies have described a prolonged duration of analgesia when DEX was added to ropivacaine for regional nerve blocks [ 22 , 23 ].…”
Section: Regional Blocksmentioning
confidence: 99%
“…Dexmedetomidine (DEX), a selective agonist of α2-adrenergic receptors, can be an effective adjuvant to local anesthetics for peripheral nerve blocks [ 22 , 23 ]. Preclinical and clinical studies have described a prolonged duration of analgesia when DEX was added to ropivacaine for regional nerve blocks [ 22 , 23 ]. One clinical trial found that ultrasound-guided ISB with DEX in ARCR led to a significantly lower mean VAS score and a significantly higher mean patient satisfaction score within 48 hours postoperatively, showing lower mean interleukin (IL)-6 and IL-8 levels than ISB alone with delayed rebound pain [ 22 ].…”
Section: Regional Blocksmentioning
confidence: 99%
See 2 more Smart Citations